PENGEMBANGAN DAN PENERAPAN SISTEM INFORMASI DAN MANAJEMEN BERBASIS DIGITAL MELALUI APLIKASI SIBERAS DI DESA RIJANG PANUA KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - , Zulkarnain Ahmad (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study aims to implement and develop a digital-based management information system using the Siberas application (Bumdes Information System and Village/Sub-district Management) in Rijang Panua Village, Kulo District, Sidenreng Rappang Regency. This system is designed to optimize and facilitate administrative services and transparency of public information in the village. With a system design-based research methodology and a qualitative approach, this study involves several main stages: needs analysis, application design, system testing, and impact evaluation. The results of the study indicate that the Siberas application is able to optimize the village administration process, increase the accessibility of public information for the community, and speed up service time by up to 30% compared to manual methods. In addition, this application also increases user satisfaction and increases public trust in village officials. This study contributes to the development of a digital-based village information system which is expected to be implemented in other villages in Sidenreng Rappang Regency.